Súmula vinculante e jurisdição constitucional brasileira - Leite, Glauco Salomão (2007)
This work aims at researching the polemic institute of binding decision in brazilian law. In order to face the multiple questions which exist about this subject, it starts from the idea that it is inserted in the constitutional adjudication model existent in the country, contributing to the increase in the equality principle as well as the juridical safety in the application of law. This presumption is essential to comprehend the reasons why the arguments which intend to characterise the binding decision as a result of legislative activity by Federal Supreme Court are refuted, which would represent a violation to the separation of powers. Similarly, it contests the idea that the binding decision is offensive to the judicial discretion, always taking into account the duty of the Federal Supreme Court as a superior organ in the interpretation of the Constitution. From this, it analyses the legal regime which disciplines the creation, revision and cancellation processes of the binding decisions. Furthermore, it searches the consequences derived from the binding effects of such decisions. Lastly, it makes a reoccurring comparison between the binding decisions and other institutes of the foreign law